2011
DOI: 10.1016/j.ajodo.2009.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of well-balanced lip position by Japanese orthodontic patients

Abstract: These results suggest that, when we formulate a treatment plan, we should ask the patients about lip position before we start treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
1
24
1
6
Order By: Relevance
“…These results might be attributed to the similar age of the survey participants in this study (mean age, 28.9 ±3.3 years) and those in the study by Park et al32 However, they demonstrated that middle-aged (40–54 years; mean age, 47 years) as well as older individuals (55–70 years; mean age, 62 years) preferred a slightly retrusive chin as an esthetically pleasing one. In addition, Shimomura et al20 suggested that as one's age passes the thirties, one tends to prefer a slightly retrusive chin to a protrusive one. Therefore, future studies should include survey participants from various age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results might be attributed to the similar age of the survey participants in this study (mean age, 28.9 ±3.3 years) and those in the study by Park et al32 However, they demonstrated that middle-aged (40–54 years; mean age, 47 years) as well as older individuals (55–70 years; mean age, 62 years) preferred a slightly retrusive chin as an esthetically pleasing one. In addition, Shimomura et al20 suggested that as one's age passes the thirties, one tends to prefer a slightly retrusive chin to a protrusive one. Therefore, future studies should include survey participants from various age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous two-dimensional methods, including silhouettes, photographs, and digitally modified images, have been used to investigate the preferred chin projection,216171819 these methods have some limitations in terms of evaluating the esthetic chin position, such as unrealistic impression and distortion of the facial images 52021. Recently three-dimensional (3D) morphing programs have been introduced to predict soft-tissue changes related to orthodontic treatment and/or orthognathic surgery 2223.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that in Japanese people, the upper lip coincides with the E-line and the lower lip is located outside the E-line [23]; however, for an esthetically pleasing facial profile, the upper and lower lips should both coincide with the E-line [24,25]. Results of a questionnaire of 150 people over 15 years of age also indicated that the upper and lower lips should be positioned approximately 1-4 mm posterior to the E-line [26], suggesting that Westernized facial profiles are becoming more popular in the Japanese population [27].…”
Section: Esthetic Factor Esthetic Criteriamentioning
confidence: 98%
“…(FOSTER, 1973;CZARNECKI;NANDA;CURRIER, 1993;COLEMAN et al, 2007). (IGLESIAS-LINARES et al, 2011;SHIMOMURA et al, 2011;MACIAS GAGO;ROMERO MAROTO;CREGO, 2012). Foi utilizado o recurso automático do Dolphin Imaging 11.5 que, quando acionado, gira a imagem para que um determinado plano esteja paralelo à margem horizontal da radiografia.…”
Section: Uso Da Sobra Do Perfilunclassified